Contemporary challenges in the Asset Liability Management - Lubinska, Beata (Research Papers of Wrocław University of Economics, 2018)
The role of the active management of the banking book in the banking industry is constantly growing. The efficient and productive use of a bank’s resources subject to consolidated risk and return appetite remains of upmost importance for banks of all sizes. Therefore, the use of optimization techniques to manage the banking book of a financial institution is becoming an imperative to remain profitable. This article states that application of the optimization techniques can provide useful information to understand the target structure for the banking book in terms of its composition of liabilities and is an important tool to decrease the overall cost of funding. Moreover, the application of the optimization techniques in this article is seen as the integration of the exposure to the financial risks into one approach
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2018, Nr 519, s. 135-145
Keywords: optimization model; interest rate risk in the banking book; liquidity risk; objective function; constraints functions; model optymalizacji; ryzyko stopy procentowej w książce bankowej; ryzyko płynności; funkcja celu; funkcje ograniczeń